SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS PENGGUNAAN E-LKPD DALAM PEMBELAJARAN MATEMATIKA TERHADAP HARD SKILL SISWA - Sabrina Azzahra, Difa; Nindiasari, Hepsi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Although numerous studies have been conducted on the use of E-LKPD in mathematics classes, comprehensive investigations into its effectiveness in developing students’ hard skills remain limited. This study aims to analyze the effectiveness of E-LKPD in developing hard skills among students in secondary education, higher education, and vocational training schools, while also identifying the instructional models employed and the mathematical skills most frequently promoted. The research methodology involved conducting a systematic literature review (SLR) in accordance with the PRISMA guidelines, utilizing Google Scholar via Publish or Perish for the period from 2020 to 2025. The papers analyzed were published in accredited domestic journals listed in at least the SINTA Index 4, and a total of 15 papers met the selection criteria. The results of this study indicate that E-LKPD effectively contributes to improving problem-solving skills, mathematical expression, logical thinking, critical thinking, mathematical communication, and academic performance. The most frequently used learning model was Problem-Based Learning (PBL), followed by Discovery Learning. These results confirm that E-LKPD is a useful alternative digital learning resource that supports active mathematics learning and can strengthen students’ hard skills.